2021
DOI: 10.1037/edu0000545
|View full text |Cite
|
Sign up to set email alerts
|

Not all sentences are created equal: Evaluating the relation between children’s understanding of basic and difficult sentences and their reading comprehension.

Abstract: The sentences in texts are far more complex and diverse than those that children commonly encounter in oral language. This raises interesting questions as to whether the understanding of some sentence types might be more important than others in children's reading comprehension. Accordingly, we examined the relation between children's reading comprehension and their understanding of two types of sentences: one we label as basic sentences, which are common in both oral and written language, and the other we lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 64 publications
2
22
1
Order By: Relevance
“…Understanding the individual words within a text is an essential component of establishing the meaning of that text [Perfetti & Stafura, 2014]. The larger event descriptions that result from combining these words into sentences are also an essential component of understanding because sentences convey information about what actually happened (e.g., “The puppy happily chased the boy” vs. “the boy happily chased the puppy”) [Poulsen & Gravgaard, 2016; Sorenson Duncan, Mimeau, Crowell, & Deacon, 2020]. The comparable magnitude of the relations between vocabulary and syntax to reading comprehension emphasizes that, as Kirby and Savage [2008] have argued for typical readers, to understand reading comprehension in children with ASD, the particular language skills encompassed under the oral language umbrella must be delineated.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the individual words within a text is an essential component of establishing the meaning of that text [Perfetti & Stafura, 2014]. The larger event descriptions that result from combining these words into sentences are also an essential component of understanding because sentences convey information about what actually happened (e.g., “The puppy happily chased the boy” vs. “the boy happily chased the puppy”) [Poulsen & Gravgaard, 2016; Sorenson Duncan, Mimeau, Crowell, & Deacon, 2020]. The comparable magnitude of the relations between vocabulary and syntax to reading comprehension emphasizes that, as Kirby and Savage [2008] have argued for typical readers, to understand reading comprehension in children with ASD, the particular language skills encompassed under the oral language umbrella must be delineated.…”
Section: Discussionmentioning
confidence: 99%
“…Two of these studies, both with students in grade 5, yielded diverging results. Poulsen andGravgaard (2016) andSorenson Duncan et al (2021) investigated how students' processing of basic (i.e., active and subject-relative clause) and difficult (i.e., passive and object-relative clause) sentences influence reading comprehension. Poulsen and Gravgaard found that response times to difficult, but not basic, sentences made unique and direct contributions to reading comprehension.…”
Section: How Different Sentence Types Contribute To Reading Comprehensionmentioning
confidence: 99%
“…One research-informed understanding about language comprehension skills is that they entail much more than comprehending word meanings. Research has suggested that despite strong predictive associations between vocabulary knowledge and reading comprehension (Ahmed et al, 2016;Quinn, Wagner, Petscher, & Lopez, 2015;Wright & Cervetti, 2017), interventions that primarily target vocabulary, or knowledge of word parts, often fail to move reading comprehension outcomes (Deshler, Palincsar, Biancarosa, & Nair, 2007 (Cain & Nash, 2011;Crosson & Lesaux, 2013;Deacon & Kieffer, 2018;Lorch, 1989;Sorenson Duncan, Mimeau, Crowell, & Deacon, 2020), knowledge of specialized and general vocabulary (Ahmed et al, 2016;Crosson, McKeown, Robbins, & Brown, 2019;Greenleaf, Brown, & Litman, 2004;Quinn et al, 2015), awareness of meaningful word parts (Nagy, Carlisle, & Goodwin, 2014), familiarity with text structures (Giulia Cataldo & Oakhill, 2000;Meyer & Ray, 2017), and comprehension of language needed to make logical inferences (Kendeou, van den Broek, White, & Lynch, 2009). In other words, vocabulary knowledge, although essential to text comprehension, is not the only language resource used by skilled readers.…”
Section: Key Understanding 1: Comprehending Academic Texts Entails Dementioning
confidence: 99%
“…Indeed, even proficient word readers must develop new language resources to navigate middle‐grade texts focused on abstract concepts and unfamiliar content (Language and Reading Research Consortium, 2015; Language and Reading Research Consortium & Chiu, 2018; Lonigan, Burgess, & Schatschneider, 2018). These language resources comprise multiple linguistic dimensions: syntactic awareness (Cain & Nash, 2011; Crosson & Lesaux, 2013; Deacon & Kieffer, 2018; Lorch, 1989; Sorenson Duncan, Mimeau, Crowell, & Deacon, 2020), knowledge of specialized and general vocabulary (Ahmed et al, 2016; Crosson, McKeown, Robbins, & Brown, 2019; Greenleaf, Brown, & Litman, 2004; Quinn et al, 2015), awareness of meaningful word parts (Nagy, Carlisle, & Goodwin, 2014), familiarity with text structures (Giulia Cataldo & Oakhill, 2000; Meyer & Ray, 2017), and comprehension of language needed to make logical inferences (Kendeou, van den Broek, White, & Lynch, 2009). In other words, vocabulary knowledge, although essential to text comprehension, is not the only language resource used by skilled readers.…”
Section: Readers’ Academic Language Skills and Social Practices: Thrementioning
confidence: 99%